eDNA metabarcoding for qualitative and semi-quantitative assessment of phytoplankton towards eco-sustainable mariculture in the Mediterranean Sea - Zangaro, Francesco; Vadrucci, Maria Rosaria; Ismailaj, Mariola; Specchia, Valeria; Pinna, Maurizio (Frontiers in Marine Science, 2025)
Phytoplankton communities play a crucial role in the sustainability of mariculture practices, particularly regarding the risks associated with potentially harmful species that can cause algal blooms and toxin production. These harmful species can have devastating effects, not only threatening human health and safety through the contamination of seafood and water supplies but also disrupting the delicate balance of marine ecosystems. Monitoring phytoplankton levels and composition is essential to ensure that mariculture remains environmentally sustainable, economically viable, and safe for consumers. Ultimately, this contributes to the preservation of marine biodiversity and its long-term health. Traditional methods for phytoplankton identification are often labor-intensive and may fail to capture the full diversity of these organisms. Environmental DNA (eDNA) metabarcoding is emerging as an innovative tool that offers a more comprehensive assessment of phytoplankton biodiversity, although it does not yet provide a strictly quantitative measure. In our research, we employed eDNA metabarcoding to analyze eukaryotic phytoplankton community composition, both qualitatively and semi-quantitatively, along a mariculture facility located in the Mediterranean Sea. From a quantitative perspective, we evaluated whether the number of sequences obtained for each OTU could serve as an indicator of the relative abundance of each taxonomic group across different sites. We considered five sampling sites around and at the center of the mariculture facility and conducted eDNA metabarcoding analyses with three replicates per site. Statistical analysis revealed that the number of sequences per OTU were significantly consistent among replicates. This suggests that the number of sequences can be used as a proxy concerning the relative abundance of taxonomic groups across sampling sites. Consequently, this research opens the possibility of using eDNA metabarcoding as a semi-quantitative tool. From a qualitative perspective, we were able to characterize the structure of eukaryotic phytoplankton communities around the mariculture plant, detecting a high level of biodiversity. We also identified potentially dangerous species at low abundance, highlighting the potential of eDNA metabarcoding as an early warning system, an essential aspect for ensuring sustainability in mariculture. This study represents a pioneering effort in utilizing eDNA metabarcoding for both the semi-quantitative and qualitative monitoring of eukaryotic phytoplankton in mariculture supporting eco-sustainable management practices.